Indeterminate Colitis – Update on Treatment Options - Venkateswaran N; Weismiller S; Clarke K (Dove Medical Press, 2021)
Niranjani Venkateswaran,1 Scott Weismiller,1 Kofi Clarke2 1Division of General Internal Medicine, Department of Medicine, Pennsylvania State University College of Medicine, Hershey, PA, USA; 2Division of Gastroenterology and Hepatology, Department of Medicine, Pennsylvania State University College of Medicine, Hershey, PA, USACorrespondence: Kofi ClarkeDivision of Gastroenterology and Hepatology, Department of Medicine, Pennsylvania State University College of Medicine, 500 University Drive, Hershey, PA, 17033, USATel +1 717-531-8741Fax +1 717-531-6770Email kclarke@pennstatehealth.psu.eduAbstract: Indeterminate colitis (IC) is described in approximately 5- 15% of patients with inflammatory bowel disease (IBD). It usually reflects a difficulty or lack of clarity in distinguishing between ulcerative colitis (UC) and Crohn's disease (CD) on biopsy or colectomy specimens. The diagnostic difficulty may explain the variability in the reported prevalence and incidence of IC. Clinically, most IC patients tend to evolve over time to a definite diagnosis of either UC or CD. IC has also been interchangeably described as inflammatory bowel disease unclassified (IBDU). This review offers an overview of the available limited literature on the conventional medical and surgical treatments for IC. In contrast to the numerous studies on the medical management of UC and CD, there are very few data from dedicated controlled trials on the treatment of IC. The natural evolution of IC more closely mimics UC. Regarding medical options for treatment, most patients diagnosed with IC are treated similarly to UC, and treatment choices are based on disease severity. Others are managed similarly to CD if there are features suggestive of CD, including fissures, skin tags, or rectal sparing. In medically refractory IC, surgical treatment options are limited and include total proctocolectomy (TPC) and ileal pouch-anal anastomosis (IPAA), with its associated risk factors and complications. Post-surgical complications and pouch failure rates were historically thought to be more common in IC patients, but recent meta-analyses reveal similar rates between UC and IC patients. Future therapies in IBD are focused on known mechanisms in the disease pathways of UC and CD. Owing to the lack of IC-specific studies, clinicians have traditionally and historically extrapolated the data to IC patients based on their symptomatology, clinical course, and endoscopic findings.Keywords: indeterminate colitis, medical treatment, ulcerative colitis, Crohn's disease, total proctocolectomy, ileal pouch-anal anastomosis